2022
DOI: 10.3390/toxics10060329
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and the Dermal Absorption of Bromochlorophene, a Cosmetic Preservative Ingredient, in Rats

Abstract: The cosmetic industry has flourished in recent years. Accordingly, the safety of cosmetic ingredients is increasing. Bromochlorophene (BCP) is a commonly used cosmetic preservative. To evaluate the effects of BCP exposure, in vitro dermal absorption and in vivo pharmacokinetic (PK) studies were conducted using gel and cream formulations. The Franz diffusion cell system and rat dorsal skin were used for tests according to the Korea Ministry of Food and Drug Safety guidelines for in vitro skin absorption methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This study showed the dermal absorption rate of pyrogallol using a Franz diffusion cell, which has been frequently used for in vitro dermal absorption studies [ 23 ]. In order to proceed in the same way as the actual hair dye, the washing process was carried out after 30 min, and most of the exposed hair dye (48.4 ± 7.6%) was found in the washing solution (30 min).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed the dermal absorption rate of pyrogallol using a Franz diffusion cell, which has been frequently used for in vitro dermal absorption studies [ 23 ]. In order to proceed in the same way as the actual hair dye, the washing process was carried out after 30 min, and most of the exposed hair dye (48.4 ± 7.6%) was found in the washing solution (30 min).…”
Section: Discussionmentioning
confidence: 99%